A collective organizational learning model for organizational development. Issue 1 (29th November 2018) - Lau, Kung Wong; Lee, Pui Yuen; Chung, Yan Yi
Abstract : Purpose: Organizational learning is traditionally structured with conventional in-house learning models aiming to equip employees with practical skills for operational needs. In contrast, contemporary goals emphasize unstructured organizational learning provided with learning environments to facilitate employees' formal and informal knowledge creation. Therefore, the conventional organizational learning models are facing tremendous challenges, and it is crucial to change the traditional modes of practice into a new approach of collective learning and knowledge transfer. As well, the emergence of innovative business environments and tacit knowledge-based society urges a new form of organizational learning model to cope with employees' learning, knowledge transfer and even knowledge management. The paper aims to discuss these issues. Design/methodology/approach: In this study, the authors' team applied a typological review for systematically analyzing current organizational learning models aiming to modify and create a new collective model. Findings: The new model covers the strengths of existing approaches from which the fundamental 3Ps (i.e. principles, purposes and processes of organizational learning) concept is derived from incorporating a development perspective of organizational trajectories and technological innovations. Originality/value: The authors envisage that the new model can facilitate organizations to assess and adapt their organizational learning needs and orientations by applying this organic and dynamic model which emphasizes assessment in relation to the competitive environment, technological trends and organizational growth.